Strategies for managing security risk in postal traffic: Approaches, challenges and guidelines - Binički, Marijan; Škorput, Pero; Kljak, Tomislav (Crisis Management Days, 2025)
The paper investigates the management of security risks within the postal system. The focus is on analysing security risks associated with key elements and processes in postal traffic, considering the likelihood of occurrence and the consequences of potential adverse events. The paper emphasizes that complete security and protection in a technical sense are neither achievable nor economical; therefore, it proposes the application of methods for risk balancing and control using the Trade-Off method. The use of the concept of risk-tolerant intensity in operational and security assessments is suggested. The paper systematizes security risks in terms of the potential for material or non-material damage due to the exploitation of system weaknesses by threats under certain circumstances.